2019
DOI: 10.1111/cei.13289
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immunological changes in patients with LADA are a mixture of those seen in patients with type 1 and type 2 diabetes

Abstract: Summary There is currently scarce knowledge of the immunological profile of patients with latent autoimmune diabetes mellitus in the adult (LADA) when compared with healthy controls (HC) and patients with classical type 1 diabetes (T1D) and type 2 diabetes (T2D). The objective of this study was to investigate the cellular immunological profile of LADA patients and compare to HC and patients with T1D and T2D. All patients and age‐matched HC were recruited from Uppsala County. Peripheral blood mononuclear cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 59 publications
(87 reference statements)
7
35
2
1
Order By: Relevance
“…We speculate that NK cells might possess a protective property, which would explain why that the NK cell number was decreased in response of the increased IFN‐γ + cells among NK cells. In accordance with this result, we have previously found that the proportion of CD56 high NK cells, which are considered to be IFN‐γ‐producing cells, are increased in LADA patients compared to healthy controls and T2D patients, but similar to T1D patients …”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We speculate that NK cells might possess a protective property, which would explain why that the NK cell number was decreased in response of the increased IFN‐γ + cells among NK cells. In accordance with this result, we have previously found that the proportion of CD56 high NK cells, which are considered to be IFN‐γ‐producing cells, are increased in LADA patients compared to healthy controls and T2D patients, but similar to T1D patients …”
Section: Discussionsupporting
confidence: 82%
“…Neutrophils were reported to be decreased in the peripheral blood of T1D patients, indicating that they might migrate to local organs . Nevertheless, we did not find any alteration of CD15 low neutrophils in the peripheral blood of T1D patients compare to healthy controls . In the present study, we found a decreased proportion of neutrophils in PDLNs of MLDSTZ mice.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations